Effects of diethylstilbestrol exposure during gestation on both maternal and offspring behavior - Tomihara, Kazuya; Zoshiki, Takahiro; Kukita, Sayaka Y.; Nakamura, Kanako; Isogawa, Ayuko; Ishibashi, Sawako; Tanaka, Ayumi; Kuraoka, Ayaka S.; Matsumoto, Saki (Frontiers in Neuroscience, 2015)
Endocrine disruption during gestation impairs the physical and behavioral development of offspring. However, it is unclear whether endocrine disruption also impairs maternal behavior and in turn further contributes to the developmental and behavioral dysfunction of offspring. We orally administered the synthetic non-steroidal estrogen diethylstilbestrol (DES) to pregnant female C57BL/6J mice from gestation day 11–17 and then investigated the maternal behavior of mothers. In addition, we examined the direct effects of in utero DES exposure and the indirect effects of aberrant maternal behavior on offspring using the cross-fostering method. In mothers, endocrine disruption during gestation decreased maternal behavior. In addition, endocrine disruption of foster mother influenced anxiety-related behavior and passive avoidance learning of pups regardless of their exposure in utero. The influence of DES exposure in utero, irrespective of exposure to the foster mother, was also shown in female offspring. These results demonstrate the risks of endocrine disruptors on both mother as well as offspring and suggest that developmental deficits may stem from both in utero toxicity and aberrant maternal care.